AKIBAT HUKUM TERHADAP PERKAWINAN ANAK DIBAWAH UMUR TANPA PENGAJUAN DISPENSASI KAWIN DI PENGADILAN - Komang Tri Sundari Dewi; I Nyoman Bagiastra (Program Studi Ilmu Hukum Fakultas Hukum dan Ilmu Sosial Universitas Pendidikan Ganesha Singaraja, 2024)
This research aims to find out what the legal consequences are for the marriage of minors without applying for a marriage dispensation in court. This research uses a normative juridical research method with a type of approach, namely a statutory approach and a conceptual approach. The legal materials used are primary, secondary and tertiary legal materials, obtained by conducting literature studies. The results of this research show that the state does not recognize the marriage of minors without submitting a marriage dispensation to the Court so that the marriage cannot be registered at the Religious Affairs Office (KUA) for those who are Muslim, and at the Population and Civil Registration Office.